Exploring the potential of natural feed additives from herbs as an alternative to antibiotic growth promoters for Mojosari layer duck (Anas javanica) farming: in-silico and in-vivo studies - I. H. Djunaidi; C. A. Damayanti; S. Wibowo; O. Sjofjan (Diponegoro University, 2023)
Using synthetic feed additive, such as antibiotic growth promoters (AGPs), is common in Mojosari layer duck (Anas javanica) farms. Their purpose is to enhance growth and productivity. However, the indiscriminate use of AGPs has been associated with the emergence of bacterial resistance. This leads to lingering effects and potential health hazards for poultry and consumers. In light of these concerns, natural herb feed additives have emerged as an alternative strategy to AGPs in poultry feed. The active compounds in natural feed additives can improve feed efficiency and enhance production performance, resulting in higher-quality poultry products, especially eggs. However, it is known that the active compounds in phytobiotics derived from herbs contain anti-nutrients that can affect productivity and alpha-amylase in poultry. This study was aimed to investigate the interconnection between active compounds in phytobiotics and alpha-amylase using in-silico methods and verify the findings with field data using in-vivo methods. Alpha-Amylase is a vital enzyme that catalyzes the hydrolysis of the glycosidic bonds present in glycogen, resulting in the formation of maltose, a water-soluble disaccharide. Based on the results of docking involving nine phytobiotic compounds and their interaction with glycogen, it was observed that andrographidine E showed a binding affinity of 8.8 kcal/mol. Furthermore, these compounds form conventional hydrogen bonds, facilitated the formation of stable bonds between proteins and compounds. In particular, the interacting amino acids did not exhibit unfavourable bonds. Therefore, andrographidine E was more stable compared to other compounds. Nonetheless, the results show that several compounds have weaker binding affinity than the enzyme's binding to glycogen. However, the hydrophobic binding types of these compounds did not seem to impact the performance of the alpha-amylase enzyme, as demonstrated by in vivo data.